The Global Reach of AI: A Postcolonial Analysis of Technological Dominance (International Journal of Scientific Research in Science and Technology, 2024)
In recent years, the concept of colonisation has transcended its historical confines and manifested in the digital realm through the proliferation of artificial intelligence (AI) and robotics. This paper explores the phenomenon of "robotic colonisation" in the digital world within the framework of postcolonial studies. Drawing from postcolonial theory, which critiques power dynamics, identity politics and cultural hegemony, this research examines how AI technologies from developed countries extend influence and control over less-developed nations, akin to historical colonial practices. The analysis considers economic, cultural and ethical implications, questioning the ramifications of digital colonisation on sovereignty, labour markets and human rights. By contextualizing robotic colonisation in the digital age through a postcolonial lens, this paper aims to provoke critical discourse on the complexities and inequalities arising from the global preparation of AI and robotics. The concept of robotic colonisation in the digital world extends beyond economic and cultural dimensions; it also profoundly impacts psychological and humanitarian aspects. This paper explores the psychological implications of digital colonisation through the lens of humanitarian viewpoints, within the framework of postcolonial theory. Drawing on literature from psychology, ethics, and humanitarian studies, it examines how AI technologies influence individual and collective psyche, addressing issues of identity, agency, and well-being. By integrating these perspectives, the research aims to enrich the discourse on digital colonisation, highlighting the human dimensions often overlooked in technological discussions.